RANCANGAN PEMBENAHAN BENGKEL KHUSUSNYA SOP, DESIGN LAYOUT, SISTEM ANTRIAN, DAN LAYANAN PURNAJUAL SEPEDA MOTOR HONDA DI PT EKA PRIMA MANDIRI SENTOSA SURABAYA - Steven Setiaputra Hermawan (Mechanova, 2016)
PT Eka Prima Mandiri Sentosa Surabaya is one of the authorized workshops for new Hondamotorcycle or commonly referred to as AHASS (Astra Honda Authorised Service Station). Thesales volume of motorcycles during the initial 6 months of the acquisition of the company is stillvaried, the lowest sales in April are as many as 192 units. Meanwhile, there is the highest salesin September a number of 408 units. The number of visits service was not stable from April toSeptember 2016. Several consumer complaints about the workshop, among others: 1) part of theworkshop is still not running as well as it should, so it has not reached the expected quality andproductivity because they refused consumers who want to do service; 2) a consumer complaintwhere a waiting period of service up to 2 hours or even more; 3) there are two mechanics andone trusters only, so that the work becomes old; 4) there are many parts that run out and have tobuy the first time they change them. The final task was created with the aim to: 1) create SOPworkshop, so mechanics can improve productivity and quality of service to consumers wherethey can wait for the light service without complaint + 10-15 minutes, while waiting 25-30minutes for service with complaints and replacement of parts; 2) adjust the layout of theworkshop layout is effective and efficient; 3) create a proper queuing system in an effort to serveall customers who come in, so as not to be disappointed and no denial of service again; 4)explain the program after sales service that consumers are satisfied, and HR PT Eka PrimaMandiri Sentosa understand this as a guide to performance. Based on the study of literature andthe process of apprenticeship by the author, is because there is no standard operationalprocedure (SOP) for special workshops, and layout workshop not well ordered with the tracks,the queuing system is chaotic, and consumers are less information about the program after salesservice offered workshops. To that end, the author offers some solutions: 1) design the flow ofSOP and quality guidelines workshop; 2) organize and reorganize the layout of the workshop; 3)designing queuing systems workshop; 4) create post-sale service program.